Analisis Kemampuan Literasi Numerasi dalam Menyelesaikan Soal HOTS Materi Bangun Ruang Siswa Kelas V SD - Pramesthi, Rahma Indar; Suryatin, Suryatin; Erviana, Lina (PGSD STKIP PGRI Pacitan, 2022)
This research aims to find out: (1) the numeracy literacy ability of class V students in solving the HOTS questions on spatial construction materials; (2) the ability of numeracy literacy in male students of class V in solving HOTS questions on space construction; (3) the numeracy literacy ability of female students in class V in solving the HOTS questions on spatial construction. This type of research was qualitative descriptive research. The subject of the research is all V class students at Pucangsewu State Elementary School in the even semester of the 2021/2022 academic year. Data collection used interview, test, and documentation techniques. Test the validity of the data using triangulation techniques followed by data analysis that includes data reduction, data presentation, and verification. The results of this research showed that (1) Pucangsewu State Elementary School V class students with a moderate level of numeracy literacy ability of as much as 33.33%, sufficient as much as 53.34%, and low as much as 13.33%; (2) Class V male students of Pucangsewu State Elementary School with 42.86% medium level numeracy literacy ability, 42.86% sufficient, and 14.28% low level; (3) Class V female students of Negeri Pucangsewu Elementary School with a moderate literacy level of 25%, 62.5% sufficient, and 12.5% ​​low.